2016
DOI: 10.1016/j.molcel.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics Analyses Reveal Temporal and Spatial Lipid Organization and Uncover Daily Oscillations in Intracellular Organelles

Abstract: Cells have evolved mechanisms to handle incompatible processes through temporal organization by circadian clocks and by spatial compartmentalization within organelles defined by lipid bilayers. Recent advances in lipidomics have led to identification of plentiful lipid species, yet our knowledge regarding their spatiotemporal organization is lagging behind. In this study, we quantitatively characterized the nuclear and mitochondrial lipidome in mouse liver throughout the day, upon different feeding regimens, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 33 publications
(47 reference statements)
9
101
0
Order By: Relevance
“…5), similar to previous analyses in mouse liver (17). Whereas such changes in amplitude are smaller than for diurnal transcript oscillations, they represent substantial differences in membrane homeostasis across 24 h.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…5), similar to previous analyses in mouse liver (17). Whereas such changes in amplitude are smaller than for diurnal transcript oscillations, they represent substantial differences in membrane homeostasis across 24 h.…”
Section: Discussionsupporting
confidence: 86%
“…This effect was characteristic for long and very long chain PC and SM lipids, which were highly synchronized in both skeletal muscle and primary myotubes, whereas other PLs like PE did not show this preference. Remarkably, a correlation based on chain length was also observed for long and very long chain PC and SM species in WT and Per1/2 KO mice whereas the contribution of desaturation was less prominent (17). Consistent with this observation is the rhythmic gene expression of ELOVL5, ACSL4, and ACSL5 in human skeletal muscle tissue, whose peak of expression correlated with peak levels of very long chain PC and SM lipids ( Fig.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In this context, it was recently shown that the lipid composition of the nucleus and mitochondria exhibit daily rhythms. (8) The current study and the emerging open questions carry wide implications on our basic understanding of liver function in health and disease.…”
mentioning
confidence: 98%